Determinants of Exclusive Breastfeeding and Patterns of Complementary Feeding Practices in Mecca City, Saudi Arabia - S. Azzeh, Firas (International Journal of Child Health and Nutrition, 2017)
Background: The World Health Organization (WHO) recommends optimal feeding practices during infancy and early childhood for better health and growth of children. Objective: To determine the factors affecting exclusive breastfeeding (EBF) duration and the time of introducing complementary feeding (CF) in Mecca City, Saudi Arabia. Methods: This cross-sectional study recruited 814 Saudi mothers. All mothers filled out a closed questionnaire on family sociodemographics, health status of mothers and infants, and postpartum breastfeeding habits and patterns. The patterns of CF and bottle-feeding were examined, and binary logistic regression was performed. Results: The mean ± standard deviation EBF duration was 4.6 ± 2.5 months. The EBF rate showed a sharp decrease from 50.6% at birth to 14.4% at 6 months among children. Employment of mothers, weight at childbirth <2.5 kg, weight of 2.6–3 kg at child birth, postnatal disease in infants, and pacifier use for infants were associated with a low EBF rate. Intermediate education of the mother was found to increase EBF duration as compared to mothers with higher levels of education. Most mothers introduced plant-based CFs to infants at 4 months of age (median), but animal-based CFs were introduced only after 8 months (median). The median age of starting milk formula was 3 months. Conclusion and Recommendation: The reported rate of EBF is far below the current international recommendations. The patterns of CF practices and bottle-feeding differ widely from the WHO recommendations in Mecca City. National campaigns should be implemented to promote EBF in Saudi Arabia.